Producer protection legislation and termination damages in the presence of contracting frictions - Steven Y. Wu (Institute for the Study of Labor (IZA), 2009)
This study models producer protection legislation that would grant growers the right to claim damages (PPLD) if their contracts are prematurely terminated. In the absence of contracting frictions that prevent contractors from redesigning contracts to accommodate exogenous policy changes, PPLD would not be distortionary or redistributive. If contracting frictions exist, then PPLD would have efficiency and redistributive effects, though the direction and magnitude depends on the size of PPL damages vis-à-vis expected damages under existing contract law. This study clarifies the conditions under which PPLD would decrease efficiency and protect growers.
urn:nbn:de:101:1-2009100277
Keywords: Q12; Q18; K12; D82; D86; 330; Contracts; moral hazard; agricultural policy; producer protection legislation; contract law; Landwirtschaft; Lieferanten-Kunden-Beziehung; Vertragsrecht; Haftung; Moral Hazard; Theorie